Thiophene modified ferriporphyrin polymer as well as preparation method and photocatalytic application thereof

By loading the thiophene-modified iron porphyrin polymer to the mesoporous graphite phase carbon nitride surface, as a photocatalyst, the problem of catalyst instability and product separation difficulties in the prior art is solved. Achieve efficient CO2 reduction effect.

CN119259115AActive Publication Date: 2025-01-07JILIN UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411297622.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-07
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing CO2 reduction catalysts have problems with product separation difficulties and unstable catalytic performance, which limits the development of photocatalytic carbon dioxide reduction.

Method used

The thiophene modified iron porphyrin polymer is loaded onto the mesoporous graphite phase carbon nitride surface by in situ chemical polymerization. As a photocatalyst, carbon dioxide is catalyzed to carbon monoxide under visible light excitation, achieving ultra-long stable catalysis and improving product Selective.

Benefits of technology

It achieved a 120-hour ultra-long stable catalysis, with the selectivity of the product carbon monoxide up to 98%, solving the problems of product separation difficulties and unstable catalytic performance, and improving the utilization rate of light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259115A_ABST
    Figure CN119259115A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photocatalysis, in particular to a thiophene modified ferriporphyrin polymer as well as a preparation method and photocatalysis application thereof. The invention discloses a thiophene modified iron porphyrin polymer which comprises the following raw materials: iron thienyl porphyrin, mesoporous graphite phase carbon nitride and an auxiliary agent, and the weight ratio of the iron thienyl porphyrin to the mesoporous graphite phase carbon nitride to the auxiliary agent is (1-1.2): 100: (3-4). According to the thiophene-modified ferriporphyrin polymer disclosed by the invention, polythiophene porphyrin is loaded on the surface of mesoporous graphite-phase carbon nitride through an in-situ chemical polymerization method, so that the problem that a current molecular catalyst is unstable is solved; the thiophene modified ferriporphyrin polymer is used as a photocatalyst, under the excitation of visible light (lambda = 420 nm), carbon dioxide can be catalytically reduced into carbon monoxide, 120-hour ultra-long-time stable catalysis can be achieved, the selectivity of the product carbon monoxide reaches up to 98%, and the problem that the product is difficult to separate is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalysis, and in particular to a thiophene-modified iron porphyrin polymer and a preparation method and photocatalytic application thereof. Background Art

[0002] In recent years, with the improvement of social living standards and the acceleration of industrialization, global energy consumption has continued to grow and is expected to reach 27 terawatts by 2050. In addition, over-reliance on non-renewable fossil fuels to meet the growing energy demand will not only reduce limited resources, but also lead to a sharp increase in the content of carbon dioxide (CO2) in the atmosphere. From 1750 to 2023, the concentration of carbon dioxide in the atmosphere has rapidly increased from 280ppm to 422ppm, which is the main factor causing global warming. Energy crisis and environmental problems have begun to affect people's lives. Therefore, finding new green energy to replace fossil energy has become one of the hot topics of current scientific research. In nature, plants use light energy to convert carbon dioxide into glucose; inspired by this, we can use solar energy to reduce carbon dioxide (CO2RR) into some useful raw materials (such as carbon monoxide, methane, methanol, formic acid, etc.), and this idea can realize the concept of "carbon neutrality". This can not only utilize and convert CO2 in the atmosphere, but also convert inexhaustible and intermittent solar energy into storable chemical energy. It is a promising new method to solve environmental pollution and energy crisis.

[0003] However, the traditional CO2RR catalysts still have disadvantages such as difficulty in product separation and unstable catalytic performance, which limits the development of photocatalytic carbon dioxide reduction. Therefore, the development of a CO2RR photocatalyst with high product selectivity and stability has important practical and theoretical significance.

[0004] Currently, organic molecular catalysts have high catalytic performance and selectivity, but their stability is weak and difficult to recycle. Therefore, combining molecular catalysts with solid supports is a simple and effective strategy that can retain the high selectivity and activity of molecular catalysts while giving full play to the stability and recyclability of solid supports.

[0005] Currently, there is no related prior art reporting on thiophene-modified iron porphyrin polymers, preparation methods, and photocatalytic applications thereof. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the present application provides a thiophene-modified iron porphyrin polymer, which loads the polythiophene porphyrin onto the surface of mesoporous graphite phase carbon nitride by in-situ chemical polymerization, thereby solving the problem of instability of current molecular catalysts; the thiophene-modified iron porphyrin polymer is used as a photocatalyst, which can catalytically reduce carbon dioxide to carbon monoxide under the excitation of visible light (λ=420nm), and can achieve ultra-long-term stable catalysis for 120 hours, and the selectivity of the product carbon monoxide is as high as 98%, thereby solving the problem of difficult product separation.

[0007] The technical solution adopted by this application to solve its technical problem is:

[0008] The first purpose of the present application is to provide a thiophene-modified iron porphyrin polymer, comprising the following raw materials:

[0009] Iron thiophene porphyrin, mesoporous graphite phase carbon nitride, and an auxiliary agent, wherein the weight ratio of the iron thiophene porphyrin, mesoporous graphite phase carbon nitride, and the auxiliary agent is (1-1.2):100:(3-4).

[0010] In some embodiments, the auxiliary agent is anhydrous ferric chloride.

[0011] In some embodiments, the preparation process of the iron thienyl porphyrin is: adding 2-thiophenecarboxaldehyde and pyrrole to a mixed solution for reaction; after the reaction is completed, thienyl porphyrin is obtained; and thienyl porphyrin is reacted with an iron source to obtain iron thienyl porphyrin.

[0012] In some embodiments, the molar ratio of 2-thiophenecarboxaldehyde to pyrrole is 1:1.

[0013] In some embodiments, the 2-thiophenecarboxaldehyde and pyrrole are added to a mixed solution and reacted under reflux for 50-60 minutes; the mixed solution includes acetic acid, propionic acid, and nitrobenzene.

[0014] In some embodiments, the thienylporphyrin and the iron source are refluxed for 4-5 hours, and the iron source is ferrous chloride.

[0015] In some embodiments, the preparation process of the mesoporous graphite phase carbon nitride is as follows: cyanamide and an aqueous solution containing silicon dioxide are mixed, the temperature is increased to 550-560°C and kept at 550-560°C for 4-5 hours, and then dispersed, filtered and washed to obtain mesoporous graphite phase carbon nitride.

[0016] In some embodiments, the mass ratio of cyanamide to silicon dioxide is 1:1.

[0017] The second object of the present application is to provide a method for preparing a thiophene-modified iron porphyrin polymer, comprising the following steps:

[0018] S1. Preparation of iron thienyl porphyrin

[0019] Adding 2-thiophenecarboxaldehyde and pyrrole to the mixed solution for reaction; after the reaction, obtaining thienylporphyrin; reacting thienylporphyrin with an iron source to obtain iron thienylporphyrin;

[0020] S2. Preparation of Mesoporous Graphitic Carbon Nitride

[0021] Mixing cyanamide and an aqueous solution containing silicon dioxide, heating to 550-560° C. and maintaining the temperature at 550-560° C. for 4-5 hours, dispersing, filtering and washing to obtain mesoporous graphite phase carbon nitride;

[0022] S3. Thiophene-modified iron porphyrin polymer

[0023] The mesoporous graphite phase carbon nitride is dispersed, iron thiophene porphyrin and an auxiliary agent are added, and the mixture is reacted at 40-50° C. for 24-30 hours to obtain a thiophene-modified iron porphyrin polymer.

[0024] The third purpose of the present application is to provide a photocatalytic application of a thiophene-modified iron porphyrin polymer, wherein the thiophene-modified iron porphyrin polymer described above is used as a photocatalyst to catalytically reduce carbon dioxide to carbon monoxide under visible light irradiation.

[0025] The beneficial effects of the present invention are:

[0026] 1. The thiophene-modified iron porphyrin polymer provided in this application loads the polythiophene porphyrin onto the surface of mesoporous graphite phase carbon nitride by in-situ chemical polymerization, thus solving the problem of instability of current molecular catalysts;

[0027] 2. The thiophene-modified iron porphyrin polymer provided in the present application uses mesoporous graphite phase carbon nitride as a carrier, which can transfer photogenerated electrons to the metal catalytic sites of thiophene porphyrin after being excited by visible light, thereby avoiding a large amount of electron-hole recombination and improving the catalytic activity.

[0028] 3. The thiophene-modified iron porphyrin polymer provided in the present application, as a photocatalyst, can catalytically reduce carbon dioxide to carbon monoxide under the excitation of visible light (λ=420nm), can achieve ultra-long-term stable catalysis for 120 hours, and the selectivity of the product carbon monoxide is as high as 98%, solving the problem of difficult product separation.

[0029] 4. The thiophene-modified iron porphyrin polymer provided in the present application has good absorption in the visible light region when used as a catalyst, which solves the problem that traditional inorganic semiconductors need to use ultraviolet light for catalysis and greatly improves the utilization rate of light. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0031] Figure 1 This is the NMR image of the thiophene porphyrin prepared in Example 1;

[0032] Figure 2 X-ray powder diffraction (XRD) patterns of mpg-CN and p-FeTThP|mpg-CN prepared in Example 1;

[0033] Figure 3 This is the UV-visible absorption spectrum of the p-FeTThP|mpg-CN catalyst prepared in Example 1;

[0034] Figure 4 TEM image of the p-FeTThP|mpg-CN catalyst prepared in Example 1;

[0035] Figure 5 A graph showing the change in the yield of CO produced by the p-FeTThP|mpg-CN catalyst prepared in Example 1 under visible light conditions when photocatalyzing CO2 to produce CO;

[0036] Figure 6 This is a diagram showing the yield and selectivity of the p-FeTThP|mpg-CN catalyst prepared in Example 1 to generate CO under visible light conditions by photocatalysis of CO2;

[0037] Figure 7 This is a graph showing the change in the yield of CO produced by the p-FeTThP|mpg-CN catalyst prepared in Example 1 when the FeTThP ratio is 1.2 under visible light conditions when CO2 is photocatalyzed;

[0038] Figure 8 This is a graph showing the CO production of FeTThP prepared in Comparative Example 1 and p-FeTThP|mpg-CN prepared in Example 1 when irradiated with visible light for 24 hours;

[0039] Fig. 9 This is a graph showing the CO and H2 production of mpg-CN prepared in Comparative Example 2 and p-FeTThP|mpg-CN prepared in Example 1 when irradiated with visible light for 24 hours. DETAILED DESCRIPTION

[0040] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.

[0041] As used herein, "and / or" includes the term of any and all combinations of one or more associated listed items. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "a", "an", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It is further understood that "including", when used in this specification, specifies the stated features, integers, steps, operations, elements and / or compositions, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions and / or combinations thereof.

[0042] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It is further understood that terms, such as defined in commonly used dictionaries, are interpreted in accordance with their meanings in the context of the relevant art and are not in an idealized or overly formal sense unless explicitly so defined herein.

[0043] The exemplary invention described herein may appropriately lack any one or more element limitations that are not specifically disclosed herein. Therefore, the terms "comprise", "include", "contain", etc. should be understood broadly and non-restrictively. In addition, the terminology used herein is used as a description, not a limitation, and it is unintentional to use these terminology expressions that do not include any equivalent characteristics, but only describe some of their characteristics, but various modifications are possible within the scope of the present invention according to the rights. Therefore, although the present invention has been specifically disclosed by preferred embodiments and optional features, the modifications disclosed herein to embody the changes of the present invention may be recorded by those skilled in the art, and such modifications and changes will be considered to be within the scope of the present invention.

[0044] The raw materials or reagents used in the embodiments of the present invention and the comparative examples are all purchased from mainstream manufacturers in the market. The manufacturer or concentration is not specified, and they are all analytically pure raw materials or reagents that can be routinely obtained. As long as the expected effect can be achieved, there is no particular restriction. The instruments and equipment used in the present embodiment are all purchased from major manufacturers in the market. As long as the expected effect can be achieved, there is no particular restriction. If specific techniques or conditions are not specified in the present embodiment, the techniques or conditions described in the literature in this area or according to the product specification are carried out.

[0045] After long-term use, the activity of current photocatalysts is prone to decline, resulting in reduced catalytic efficiency; and many inorganic semiconductor photocatalysts require ultraviolet light excitation, while the proportion of ultraviolet light in sunlight is relatively low, which limits the practical application of catalysts. To this end, the present application provides a thiophene-modified iron porphyrin polymer for photocatalyst, comprising the following raw materials: iron thiophene porphyrin, mesoporous graphite phase carbon nitride, and an additive, wherein the weight ratio of the iron thiophene porphyrin, mesoporous graphite phase carbon nitride, and the additive is (1-1.2):100:(3-4).

[0046] Specifically, the weight ratio of the iron thiophene porphyrin, mesoporous graphite carbon nitride, and additive is 1:100:3. For example, the weight ratio of the iron thiophene porphyrin, mesoporous graphite carbon nitride, and additive is 1.2:100:4, or the weight ratio of the iron thiophene porphyrin, mesoporous graphite carbon nitride, and additive is 1.1:100:3.5, or the weight ratio of the iron thiophene porphyrin, mesoporous graphite carbon nitride, and additive is 1:100:4.

[0047] Current traditional molecular catalysts such as iron porphyrin, although they have high catalytic activity, often have the problem of poor stability. The above technical solution, by combining iron thienyl porphyrin with mesoporous graphitic carbon nitride and utilizing the stability and carrier effect of mpg-CN, significantly improves the overall stability of the catalyst, and the catalyst can maintain high catalytic performance even under long-term illumination and reaction conditions.

[0048] Mesoporous graphitic carbon nitride (mpg-CN) is a metal-free organic photosensitizer with excellent stability and visible light response. Its mesoporous structure not only increases the specific surface area and improves the adsorption performance of the catalyst, but also provides abundant sites for the loading of iron thiophene porphyrin. Under visible light irradiation, mpg-CN can be excited to generate photogenerated electrons and holes, which can be rapidly transferred to the catalytic sites of FeTThP through the conduction band of mpg-CN to participate in the reduction reaction of carbon dioxide.

[0049] Therefore, in this application, iron thiophene porphyrin (FeTThP) is polymerized on the surface of mesoporous graphite phase carbon nitride (mpg-CN) by in-situ chemical polymerization, which not only achieves the close combination of molecular catalyst and solid support, but also promotes the effective separation and transfer of photogenerated electrons and holes; this method avoids the rapid recombination of electrons and holes in traditional catalysts and improves the catalytic efficiency. At the same time, the polymerization process enhances the structural stability of the catalyst, enabling it to maintain efficient catalytic performance for a long time.

[0050] The method for preparing the above-mentioned thiophene-modified iron porphyrin polymer comprises the following steps:

[0051] S1. Preparation of iron thienyl porphyrin

[0052] 2-thiophenecarboxaldehyde and pyrrole are added to the mixed solution, and the mixture is reacted under reflux for 50-60 minutes. After the reaction is completed, thienylporphyrin (TThP) is obtained; thienylporphyrin and an iron source are reacted under reflux for 4-5 hours to obtain iron thienylporphyrin (FeTThP);

[0053] S2. Preparation of Mesoporous Graphitic Carbon Nitride

[0054] Mixing cyanamide and an aqueous solution containing silicon dioxide, heating to 550-560° C. and maintaining the temperature at 550-560° C. for 4-5 hours, dispersing, filtering and washing to obtain mesoporous graphite phase carbon nitride;

[0055] S3. Thiophene-modified iron porphyrin polymer

[0056] The mesoporous graphite phase carbon nitride is dispersed, iron thiophene porphyrin and an auxiliary agent are added, and the mixture is reacted at 40-50° C. for 24-30 hours to obtain a thiophene-modified iron porphyrin polymer.

[0057] Specifically, in step S1, the molar ratio of 2-thiophenecarboxaldehyde to pyrrole is 1:1, and the added volume of the mixed solution is 10 times the volume of pyrrole; the volume ratio of acetic acid, propionic acid, and nitrobenzene in the mixed solution is 4:4:1; and the iron source is ferrous chloride;

[0058] It can be understood that the preparation of TThP is to further introduce iron ions through metallization reaction (reaction with FeCl2·4H2O) to obtain FeTThP with higher catalytic activity and selectivity; in addition, the introduction of TThP can also enhance the electronic conductivity and stability of the material, which is crucial to improving the performance of the final photocatalyst in the photocatalytic carbon dioxide reduction reaction.

[0059] In the present application, 2-thiophene carboxaldehyde is selected as the aldehyde compound, which contains a thiophene ring, which is a heterocyclic ring with a conjugated structure and can effectively enhance the stability and electronic conductivity of the molecule;

[0060] Mixed solvent selection: A mixed solution of acetic acid, propionic acid and nitrobenzene is used as the reaction solvent. The selection of these solvents is based on their solubility in the reactants, the control of the reaction process and the convenience of subsequent treatment; acetic acid and propionic acid, as protic solvents, are conducive to the condensation reaction of pyrrole and aldehyde compounds; nitrobenzene, as an aprotic solvent, can adjust the polarity of the reaction system and promote the precipitation of the product.

[0061] Reaction condition control: The reaction is carried out under heating reflux conditions. By controlling the reaction time and temperature, the reaction is ensured to proceed fully and the formation of by-products is avoided. After the reaction is completed, the product is precipitated by natural cooling and the addition of methanol.

[0062] Post-treatment and purification: High-purity TThP is obtained by vacuum filtration, hot water and ethanol washing, and silica gel column chromatography. The key to this step is to remove impurities, ensure the purity of the product and the smooth progress of subsequent reactions.

[0063] Specifically, in step S2, the mass ratio of cyanamide to silicon dioxide is 1:1, the dispersion liquid is NH4HF2 solution, and the mass fraction of NH4HF2 in the solution is 15%.

[0064] Specifically, in step S3, the weight ratio of iron thiophene porphyrin, mesoporous graphite phase carbon nitride, and auxiliary agent is (1-1.2):100:(3-4)

[0065] On the other hand, the present application also provides a photocatalytic application of a thiophene-modified iron porphyrin polymer, wherein the thiophene-modified iron porphyrin polymer described above is used as a photocatalyst to catalytically reduce carbon dioxide to carbon monoxide under visible light irradiation. That is, the thiophene-modified iron porphyrin polymer can achieve high selectivity and long-term reduction of CO2 to CO under visible light, and has broad application prospects.

[0066] Specifically, the application method is to use acetonitrile as solvent, 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole (BIH) as sacrificial agent, add thiophene-modified iron porphyrin polymer, and realize the reduction of CO2 to CO under visible light without adding any co-catalyst.

[0067] Moreover, the traditional photocatalytic carbon dioxide reduction reaction is often accompanied by the generation of multiple by-products, resulting in low selectivity of the target product. In this application, by optimizing the structure and reaction conditions of iron thiophene porphyrin, highly selective generation of CO is achieved; experimental results show that under visible light irradiation, p-FeTThP|mpg-CN catalyst can efficiently reduce CO2 to CO with a selectivity of up to 98%.

[0068] Example 1

[0069] A method for preparing a thiophene-modified iron porphyrin polymer comprises the following steps:

[0070] S1. Preparation of iron thienyl porphyrin

[0071] 2.8 mL (0.03 mol) of 2-thiophene carboxaldehyde and 2.07 mL (0.03 mol) of freshly distilled pyrrole were added to a mixed solution of 60 mL of acetic acid, 60 mL of propionic acid and 15 mL of nitrobenzene at the same time. After reflux for 55 minutes, the reaction was naturally cooled to room temperature, and 25 mL of methanol was added and allowed to stand overnight. After vacuum filtration, the precipitate was washed with hot water and ethanol respectively until the filtrate was colorless, and the crude product was purified by silica gel column chromatography (dichloromethane as eluent) to obtain a purple-black powder.

[0072] 100 mg of thiophene porphyrin and 94 mg of FeCl2·4H2O were added to 100 mL of N,N-dimethylformamide (DMF) and refluxed for 4 hours. After the reaction was completed, the organic solvent was removed by distillation under reduced pressure. The obtained solid was washed with water until colorless to obtain a purple-black solid (iron thiophene porphyrin FeTThP).

[0073] S2. Preparation of mpg-CN

[0074] 4 g of cyanamide and 4 g of SiO2 particles in a 40% aqueous solution were mixed and stirred at 60°C overnight to obtain a white mixture. The white mixture was heated to 550°C at a rate of 2.3°C / min and maintained at this temperature for 4 hours. The obtained powder was dispersed in a 15% NH4HF2 aqueous solution and stirred overnight. After filtering, the filtrate was washed with distilled water and ethanol respectively until neutral, and dried to obtain yellow powder mpg-CN.

[0075] S3. Preparation of mpg-CN composite photocatalyst modified with iron thiophene porphyrin polymer (p-FeTThP|mpg-CN)

[0076] Disperse 100 mg of the prepared mpg-CN in 40 ml of CHCl3 and ultrasonicate for 30 min to obtain a dispersion of mpg-CN; dissolve 1 mg of FeTThP in 10 ml of CHCl3 to obtain a dispersion of FeTThP, and add the dispersion of FeTThP to the above-mentioned dispersion of mpg-CN and ultrasonicate for 30 min to obtain a mixed solution;

[0077] A CHCl3 solution containing 3 mg of anhydrous FeCl3 was added to the mixed solution, and the mixture was reacted at 40°C for 24 h under Ar protection. During the reaction, the suspension changed from yellow to dark gray. After the reaction, the suspension was cooled to room temperature and filtered. The filter cake was washed with CHCl3 and distilled water respectively until the filtrate was colorless. The filter cake was dried to obtain a composite photocatalyst.

[0078] Example 2

[0079] A method for preparing a thiophene-modified iron porphyrin polymer comprises the following steps:

[0080] In S3. preparation of the iron thiophene porphyrin polymer modified mpg-CN composite photocatalyst (p-FeTThP|mpg-CN), the weight ratio of FeTThP, mpg-CN, and anhydrous FeCl3 is 1.2:100:4, and the other conditions are the same as in Example 1.

[0081] Example 3

[0082] A method for preparing a thiophene-modified iron porphyrin polymer comprises the following steps:

[0083] In S3. preparation of the iron thiophene porphyrin polymer modified mpg-CN composite photocatalyst (p-FeTThP|mpg-CN), the weight ratio of FeTThP, mpg-CN, and anhydrous FeCl3 is 1.1:100:3.5, and the other conditions are the same as in Example 1.

[0084] Example 4

[0085] A method for preparing a thiophene-modified iron porphyrin polymer comprises the following steps:

[0086] In S3. preparation of the iron thiophene porphyrin polymer modified mpg-CN composite photocatalyst (p-FeTThP|mpg-CN), the weight ratio of FeTThP, mpg-CN, and anhydrous FeCl3 is 1:100:4, and the other conditions are the same as in Example 1.

[0087] Comparative Example 1

[0088] A method for preparing iron thienyl porphyrin comprises the following steps:

[0089] S1. Preparation of iron thienyl porphyrin

[0090] 2.8mL (0.03mol) of 2-thiophenecarboxaldehyde and 2.07mL (0.03mol) of freshly distilled pyrrole were added to a mixed solution of 60ml of acetic acid, 60ml of propionic acid and 15ml of nitrobenzene at the same time. After reflux for 55 minutes, the reaction was naturally cooled to room temperature, and 25ml of methanol was added and allowed to stand overnight. After vacuum filtration, the precipitate was washed with hot water and ethanol respectively until the filtrate was colorless, and the crude product was purified by silica gel column chromatography (dichloromethane as eluent) to obtain a purple-black powder.

[0091] 100 mg of thiophene porphyrin and 94 mg of FeCl2·4H2O were added to 100 mL of N,N-dimethylformamide (DMF) and refluxed for 4 hours. After the reaction was completed, the organic solvent was removed by distillation under reduced pressure. The obtained solid was washed with water until colorless to obtain a purple-black solid (iron thiophene porphyrin FeTThP).

[0092] Comparative Example 2

[0093] The preparation of mesoporous graphite phase carbon nitride comprises the following steps:

[0094] 4 g of cyanamide and 4 g of SiO2 particles in a 40% aqueous solution were mixed and stirred at 60°C overnight to obtain a white mixture. The white mixture was heated to 550°C at a rate of 2.3°C / min and maintained at this temperature for 4 hours. The obtained powder was dispersed in a 15% NH4HF2 aqueous solution and stirred overnight, filtered, washed with distilled water and ethanol respectively until neutral, and dried to obtain yellow powder mpg-CN.

[0095] Application Examples

[0096] Weigh 2 mg of any of the p-FeTThP|mpg-CN of Examples 1-4 and Comparative Examples 1-2, add 28 mg of BIH and 10 ml of acetonitrile, and ultrasonicate for 10 minutes. Put it into a 35 ml quartz glass reactor. Pass ultrapure CO2 gas into the reactor for 25 minutes, and use a 10W LED to simulate visible light (λ=420nm) irradiation. During the photocatalytic reaction, the gas composition after the photocatalytic reaction is detected at intervals until 120 hours.

[0097] in, Figure 1 is the NMR image of the thiophene porphyrin prepared in Example 1; Figure 1 It can be seen that there are seven groups of peaks in the figure, among which the singlet at 7.26ppm is the deuterated reagent chloroform, and the singlet at 1.6ppm is the solvent peak remaining in the experiment; the remaining five groups of peaks are all attributed to thiophene porphyrin, among which the singlet at 9.04ppm corresponds to the peripheral hydrogen of pyrrole in porphyrin, and the multiple peaks at 7.91-7.93, 7.86-7.88, and 7.51-7.53ppm are attributed to the three hydrogens of the thiophene group in porphyrin, and the singlet at -2.65ppm is the two uncoordinated hydrogens in the inner ring of porphyrin; and their peak area ratio is 4:2:2:2:1, proving that thiophene porphyrin was successfully synthesized.

[0098] Figure 2 The X-ray powder diffraction (XRD) patterns of mpg-CN and p-FeTThP|mpg-CN prepared in Example 1; Figure 2 It can be seen that compared with mpg-CN, the 002 crystal peak of the p-FeTThP|mpg-CN catalyst is significantly reduced, indicating that the iron thiophene porphyrin is successfully polymerized on the surface of mpg-CN, causing the periodic structure of mpg-CN to be destroyed;

[0099] Figure 3 is the UV-visible absorption spectrum of the p-FeTThP|mpg-CN catalyst prepared in Example 1; Figure 3 It can be seen that p-FeTThP|mpg-CN has obvious visible light response;

[0100] Figure 4 TEM image of the p-FeTThP|mpg-CN catalyst prepared in Example 1;

[0101] Figure 5 The p-FeTThP|mpg-CN catalyst prepared in Example 1 shows the change of CO production over time under visible light conditions by photocatalytic CO2 production. It can be seen from the figure that within 120 hours, the CO production increases steadily over time, indicating that the catalyst has catalytic stability and is suitable for practical applications.

[0102] Figure 6 This is a diagram showing the yield and selectivity of the p-FeTThP|mpg-CN catalyst prepared in Example 1 to generate CO by photocatalysis of CO2 under visible light conditions; as can be seen from the figure, at 120 hours, the turnover number (TON) of CO produced is 1033, and the selectivity is as high as 98%.

[0103] Figure 7 This is a graph showing how the yield of CO produced by photocatalytic CO2 under visible light conditions changes over time when the p-FeTThP|mpg-CN catalyst prepared in Example 1 has a FeTThP ratio of 1.2; as can be seen from the figure, within 120 hours, the amount of CO generated will also increase steadily with time, but at 120 hours, the TON of CO produced is 835, which is less than the p-FeTThP|mpg-CN photocatalyst with a FeTThP feed ratio of 1.

[0104] Figure 8 This is a graph showing the CO production of FeTThP prepared in Comparative Example 1 and p-FeTThP|mpg-CN prepared in Example 1 under visible light irradiation for 24 hours; as can be seen from the figure, the TON of CO produced by FeTThP in 24 hours is only 2.65, which is much smaller than 37.87 of p-FeTThP|mpg-CN, indicating that the addition of the carrier mpg-CN accelerates electron transfer and improves the catalytic activity.

[0105] Fig. 9 The figure shows the CO and H2 production of mpg-CN prepared in Comparative Example 2 and p-FeTThP|mpg-CN prepared in Example 1 under visible light irradiation for 24 hours. It can be seen from the figure that the CO produced by mpg-CN in 24 hours is 99 μmol / g, but the CO selectivity is only 50%. After the in-situ introduction of FeTThP, the CO production reaches 280 μmol / g, and the CO selectivity is increased to more than 90%. This indicates that FeTThP acts as the reaction center for CO2 reduction, reduces the energy barrier of the reaction, and improves the catalytic performance.

[0106] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A thiophene-modified iron porphyrin polymer, characterized in that: Including the following ingredients: Iron thiophene porphyrin, mesoporous graphite phase carbon nitride, and an auxiliary agent, wherein the weight ratio of the iron thiophene porphyrin, mesoporous graphite phase carbon nitride, and the auxiliary agent is (1-1.2):100:(3-4).

2. A thiophene-modified iron porphyrin polymer according to claim 1, characterized in that: The auxiliary agent is anhydrous ferric chloride.

3. A thiophene-modified iron porphyrin polymer according to claim 1, characterized in that: The preparation process of the iron thienyl porphyrin is as follows: adding 2-thiophene carboxaldehyde and pyrrole into a mixed solution for reaction; after the reaction is completed, thienyl porphyrin is obtained; and thienyl porphyrin is reacted with an iron source to obtain the iron thienyl porphyrin.

4. A thiophene-modified iron porphyrin polymer according to claim 3, characterized in that: The molar ratio of 2-thiophenecarboxaldehyde to pyrrole is 1:

1.

5. A thiophene-modified iron porphyrin polymer according to claim 3, characterized in that: The 2-thiophenecarboxaldehyde and pyrrole are added to the mixed solution and reacted under reflux for 50-60 minutes; the mixed solution includes acetic acid, propionic acid and nitrobenzene.

6. A thiophene-modified iron porphyrin polymer according to claim 3, characterized in that: The thienylporphyrin and the iron source are subjected to reflux reaction for 4-5 hours, wherein the iron source is ferrous chloride.

7. The thiophene-modified iron porphyrin polymer according to claim 1, characterized in that: The preparation process of the mesoporous graphite phase carbon nitride is as follows: cyanamide and an aqueous solution containing silicon dioxide are mixed, the temperature is raised to 550-560° C. and kept at 550-560° C. for 4-5 hours, and the mesoporous graphite phase carbon nitride is dispersed, filtered and washed to obtain the mesoporous graphite phase carbon nitride.

8. A thiophene-modified iron porphyrin polymer according to claim 7, characterized in that: The mass ratio of cyanamide to silicon dioxide is 1:

1.

9. A method for preparing a thiophene-modified iron porphyrin polymer according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Preparation of iron thienyl porphyrin Adding 2-thiophenecarboxaldehyde and pyrrole to the mixed solution to react; after the reaction, thienyl porphyrin is obtained; reacting thienyl porphyrin with an iron source to obtain iron thienyl porphyrin; S2. Preparation of Mesoporous Graphitic Carbon Nitride Mixing cyanamide and an aqueous solution containing silicon dioxide, heating to 550-560° C. and maintaining the temperature at 550-560° C. for 4-5 hours, dispersing, filtering and washing to obtain mesoporous graphite phase carbon nitride; S3. Thiophene-modified iron porphyrin polymer The mesoporous graphite phase carbon nitride is dispersed, iron thiophene porphyrin and an auxiliary agent are added, and the mixture is reacted at 40-50° C. for 24-30 hours to obtain a thiophene-modified iron porphyrin polymer.

10. A photocatalytic application of a thiophene-modified iron porphyrin polymer, characterized in that: The thiophene-modified iron porphyrin polymer described in any one of claims 1 to 8 or the thiophene-modified iron porphyrin polymer prepared by the preparation method described in claim 9 is used as a photocatalyst to catalytically reduce carbon dioxide to carbon monoxide under visible light irradiation.

Citation Information

Patent Citations

  • Metalloporphyrin / graphite-phase carbon nitride composite photocatalyst

    CN108704662A

  • Thienyl zinc porphyrin compound, synthesis thereof and application thereof in preparation of dye-sensitized solar cell

    CN111138441A

  • Preparation of porphyrin-based covalent organic framework material and application of porphyrin-based covalent organic framework material in photocatalysis

    CN116333243A